UJI TOKSISITAS DAN AKTIVITAS ANTIBAKTERI EKSTRAK DAUN MERAH TANAMAN PUCUK MERAH (Syzygium myrtifolium Walp.) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Nur Aini Haryati; Chairul Saleh; Erwin - (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
A research aims to know the toxicity of Pucuk Merah (Syzygium myrtifolium Walp.) red leaves extracts against brine shrimp Artemia salina Leach and its bioactivity against Escherichia coli and Staphylococcus aureus has been carried out. The dried samples were macerated with ethanol and were fractionated with n-hexane, ethyl acetate and ethanol-water. Phytochemical test showed the presence of alkaloids, triterpenoids, steroids, saponins, phenolic and flavonoid in ethanol extract. n-Hexane fraction contained alkaloids, triterpenoids and steroids, ethyl acetate fraction contained alkaloids, triterpenoids, phenolic and flavonoid while ethanol-water fraction contained triterpenoids, saponins and phenolic. Brine Shrimp Lethality Test showed that ethyl acetate fraction had the highest bioactivity in Artemia salina Leach with LC50 values of 149.8600 ppm. Antibacterial activity test using agar diffusion method showed that ethyl acetate fraction had the highest inhibiton against Staphylococcus aureus whereas total extract had the highest inhibition against Escherichia coli with MIC values of 0,5%. These results showed that Syzygium myrtifolium Walp. red leaves extract potential as an antibacterial agent.Keywords: Syzygium myrtifolium Walp., Toxicity, Antibacterial